Mathematical model for predicting the risk of progression of cervical dysplasia associated with papillomavirus infection in women with infertility. - Kindrativ, E. O. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. During recent decades there has been a new concept of the pathogenesis of cervical cancer, according to which dysplasia of the cervix (CIN) of CIN1 is an inflammatory process with the development of pathological regeneration that corresponds to productive papillomavirus infection and, more often, may be reversible. Morphological manifestations of moderate to severe dysplasia of the cervix are discussed in the context of neoplasia. Objective. The determination of the predictor factors and create a mathematical model for predicting the risk of progression of cervical dysplasia associated with papillomavirus infection in women with infertility. Methods. The construction of the mathematical model, regression analysis, and the values of the coefficients of multiple regression were determined using the SPSS program. Results. To determine the risk of HPVI-associated CIN progression the mathematical model was created: RP CINI=0,011*Ki-67-0,011* NKSSE/CBD +0,009*p63+0,018*age+0,032*infertility form-0,075*infertility type-0,014*duration of infertility+1,481 (constant), where, Кі-67 –the level of expression of the marker of cell proliferation, %; р63 –the level of expression of the protooncogene, %; NKSSE/CBD – height index of non-keratinized stratified squamous epithelium (NKSSE) to a capillaries bulk density (CBD); an age: number of years of the patient; infertility form: 1 – hormonal, 2 – pipe, 3 – peritoneal, 4 – combined; infertility type: 1 – primary, 2 – secondary; a duration of infertility: number of years. Individual value RP CIN is interpreted according to the differential values of the split points: [0; 1,5] – low risk of progression; [1,5; 2,5], risk of moderate CIN progression; [2,5; 3] – risk of severe CIN progression. Conclusion. The proposed program and algorithm of mathematical modeling allows us to verify the degree of severity, to calculate the digital level of progression of CIN associated with PVI in women with infertility, to form groups of clinical supervision, to choose the strategy of adequate medical tactics and to timely apply preventive methods against the progress of this disease.